Histone acetyl transferase GCN5 promotes human hepatocellular carcinoma progression by enhancing AIB1 expression. Issue 1 (December 2016) - Majaz, Sidra; Tong, Zhangwei; Peng, Kesong; Wang, Wei; Ren, Wenjing; Li, Ming; Liu, Kun; Mo, Pingli; Li, Wengang; Yu, Chundong
Abstract Background General control non-depressible 5 (GCN5) is a crucial catalytic component of a transcriptional regulatory complex that plays important roles in cellular functions from cell cycle regulation to DNA damage repair. Although GCN5 has recently been implicated in certain oncogenic roles, its role in liver cancer progression remains vague. Results In this study, we report that GCN5 was overexpressed in 17 (54.8 %) of 31 human hepatocellular carcinoma (HCC) specimens. Down-regulation of GCN5 inhibited HCC cell proliferation and xenograft tumor formation. GCN5 knockdown decreased the protein levels of the proliferation marker proliferating cell nuclear antigen (PCNA) and amplified in breast cancer 1 (AIB1), but increased the protein levels of cell cycle inhibitor p21Cip1/Waf1 in HepG2 cells. GCN5 regulated AIB1 expression, at least in part, by cooperating with E2F1 to enhance AIB1 transcription. Consistently, GCN5 expression was positively correlated with AIB1 expression in human HCC specimens in two GEO profile datasets. Conclusion Since AIB1 plays a promoting role in HCC progression, our results propose that GCN5 promotes HCC progression at least partially by regulating AIB1 expression. This study implicates that GCN5 might be a potential molecular target for HCC diagnosis and treatment.